The Onecut Transcription Factors Regulate Differentiation and Distribution of Dorsal Interneurons during Spinal Cord Development - Kabayiza, Karolina U.; Masgutova, Gauhar; Harris, Audrey; Rucchin, Vincent; Jacob, Benvenuto; Clotman, Frédéric (Frontiers in Molecular Neuroscience, 2017)
During embryonic development, the dorsal spinal cord generates numerous interneuron populations eventually involved in motor circuits or in sensory networks that integrate and transmit sensory inputs from the periphery. The molecular mechanisms that regulate the specification of these multiple dorsal neuronal populations have been extensively characterized. In contrast, the factors that contribute to their diversification into smaller specialized subsets and those that control the specific distribution of each population in the developing spinal cord remain unknown. Here, we demonstrate that the Onecut transcription factors, namely HNF-6 (or OC-1), OC-2 and OC-3, regulate the diversification and the distribution of spinal dorsal interneurons. Onecut proteins are dynamically and differentially distributed in dorsal interneurons during differentiation and migration. Analyzes of mutant embryos devoid of Onecut factors in the developing spinal cord evidenced a requirement in Onecut proteins for proper production of a specific subset of dI5 interneurons. In addition, the distribution of dI3, dI5 and dI6 interneuron populations was altered. Hence, Onecut transcription factors control genetic programs that contribute to the regulation of spinal dorsal interneuron diversification and distribution during embryonic development.